2022
DOI: 10.33429/cjas.12221.1/5
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Class of Ratio-Regression-Type Estimator under Two-Phase Sampling Scheme

Abstract: In this study, a new exponential ratio-regression estimator is developed using an auxiliary variable for estimating the finite population mean under a two-phase sampling system. The Bias and Mean Square Error (MSE) of the proposed estimator are derived and compared with some of the estimators in extant literature. Thus, the conditions under which the proposed estimator is better than some existing estimators are provided. Empirically, using four real datasets and simulation study, the proposed estimator perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…are the population means of the study and auxiliary variables. 2 represents the population variance of the study variable. 2 represents the population variance of the auxiliary variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…are the population means of the study and auxiliary variables. 2 represents the population variance of the study variable. 2 represents the population variance of the auxiliary variable.…”
Section: Methodsmentioning
confidence: 99%
“…2 represents the population variance of the study variable. 2 represents the population variance of the auxiliary variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naik and Gupta [12], Zakari et al [13] suggested the classical ratio type estimator of the population mean utilizing the auxiliary attribute under the simple random sampling as (1) Kumar and Bahl [14] suggested a ratio estimator of the population mean utilizing the auxiliary attribute under two-phase sampling as (2) The mean square error (MSE) equations of up to the first order of approximation, for Case-I and Case-II are given respectively as;…”
Section: Case-ii Givenmentioning
confidence: 99%
“…A second-phase sample can then be taken and the study variable y with an auxiliary variable x can be observed. Singh et al [1] and Muhammad et al [2] discussed that the major advantage of using two-phase sampling is the gain in high precision without a substantial increase in cost. Several authors improved ratio and regression estimators by adopting at least one auxiliary variable in two phase sampling scheme.…”
Section: Introductionmentioning
confidence: 99%